Effect of a nanoparticle-filled lubricant in turning of AISI 316L stainless steel (SS). (4th March 2017) - Rajmohan, T.; Sathishkumar, S. D.; Palanikumar, K.
ABSTRACT: Release of heat and generation of friction associated with machining operation ever posture a problem which not only reduce the tool life but also impair the quality of the product. Nano cutting fluids play a significant role in machining operations and impact tool life and quality of work. In the present work, tool flank wear is analyzed during turning AISI 316L Stainless steel (SS) under a nano cutting environment. Experiments are conducted by turning of AISI 316L SS under wet machining with and without multiwalled carbon nanotube (MWCNT) inclusions in the conventional lubricant. The second order quadratic models were developed to predict tool wear using response surface methodology (RSM) based D-optimal design. Machining parameters such as speed, feed rate, and depth of cut are chosen as numerical factors and the type of lubricant is considered as the categorical factor. The results show that the influence of the feed rate is more significant while machining the AISI 316L SS with a whisker reinforced ceramic insert. The addition of MWCNTs in SAE20W40 enhances the tool performance with their enhanced penetration. After turning experiment, a scanning electron microscope (SEM) with energy dispersive X-ray (EDS) was used to investigate the tool wear.